El cuerpo como vector de significados en el judaísmo: Un análisis sobre las relaciones entre ortodoxos y seculares en Jabad Lubavitch - Setton, Eli Damian (2007)
The aim of this paper is to analyze the interactions process between secular and orthodox Jewish of the Jabad Lubavitch movement in Buenos Aires, considering the subject’s body as a vector of meaning. The interaction processes involve the negotiation of the meanings related to the bodies, as well as the constant struggle to legitimize their position/perspective. In this process, the believers built opposite discourses, using elements that belong to the outside of the orthodox world. On the other side, secular groups confirm their condition through actions that tend to re-signify the object’s significance.